2022
DOI: 10.1021/acs.jafc.2c00274
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Effect of Bacillus subtilis YPS-32 on Potato Common Scab and Its Complete Genome Sequence Analysis

Abstract: Potato common scab is caused by Streptomyces, which resides in soil and has become a serious disease in potato planting areas worldwide. In this study, we obtained a Bacillus subtilis YPS-32 strain by natural screening, and atmospheric and roomtemperature plasma (ARTP) mutagenesis and field trial results showed that B. subtilis YPS-32 has a control efficacy of 83.70% against potato common scab. The complete genome of B. subtilis YPS-32 was sequenced, and multiple genes related to the synthesis of antibiotics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Pesticides are indispensable in agriculture and play a critical role in fulfilling rising demands for food productivity and quality. Unfortunately, environmental pollution caused by the widespread use of agrochemicals cannot be ignored. , Biological control has become a more acceptable technique to control plant diseases or pests and overcome environmental challenges. Pseudomonas species can produce a wide range of novel bioactive metabolites and play an important role in biological control. …”
Section: Introductionmentioning
confidence: 99%
“…Pesticides are indispensable in agriculture and play a critical role in fulfilling rising demands for food productivity and quality. Unfortunately, environmental pollution caused by the widespread use of agrochemicals cannot be ignored. , Biological control has become a more acceptable technique to control plant diseases or pests and overcome environmental challenges. Pseudomonas species can produce a wide range of novel bioactive metabolites and play an important role in biological control. …”
Section: Introductionmentioning
confidence: 99%
“…However, most of the present studies focus on the beneficial mechanism of probiotics on the host and few research pay attention to the genomic characteristics of probiotics. Whole genome sequence analysis can more comprehensively evaluate the safety of Bacillus subtilis and gradually deepen from traditional phenotypic analysis to molecular mechanism and genetic characteristics ( 43 , 44 ). To further understand of the genomic bioinformatics characteristics of Bacillus subtilis isolated from yaks, this study conducted the whole genome analysis to analyze the genome characteristics and functional predictions based on the previous research on the in vitro probiotic characteristics of Bacillus subtilis .…”
Section: Discussionmentioning
confidence: 99%
“…Potato common scab is one of the main diseases of potato that is di cult to control [14,15] .We previously showed that the biocontrol strain B. subtilis YPS-32 can antagonize the pathogen S. scabies, with good application results in the eld tests; however, the speci c biocontrol mechanisms are still unclear [13] . An antagonistic interaction exists between a biocontrol strain and a pathogen; when biocontrol strains are infected by a pathogen, the expression of speci c genes and proteins is up-regulated in an attempt to resist infection.…”
Section: Disscucionmentioning
confidence: 99%
“…Several studies have shown that Bacillus can produce a series of antibacterial substances, such as lipopeptides, polyketides, siderophores, and bacteriocins, which are effectively used in the biological control of plant pathogens [16,17] . For example, fengycin played a good role in the biological control of potato scab [5,13] . In this study, ve proteins involved in the biosynthetic pathway of fengycin were signi cantly up-regulated in B. subtilis YPS-32 after 24 h co-culturing with S. scabies.…”
Section: Disscucionmentioning
confidence: 99%
See 1 more Smart Citation